YUSUF DIJUAL: TANGGUNG JAWAB YEHUDA? Menelisik Kisah Yusuf dan Yehuda dalam Kej 36-50 - Petrus Christologus Dhogo (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2014)
Human trafficking, which has become a serious problem in our time, also existed centuries ago, especially when slavery was commonly accepted. The Book of Genesis shares the story of the selling by his brothers of a person named Joseph. Different from human trafficking these days, the reason for selling Joseph was more about envy than money. Envy triggered the brothers’ plot to eliminate Joseph from their family. Whatever the reason, in Egypt Joseph was put on the auction block and bought and sold as a bill of goods. The Joseph-Judah story tracks the first human trafficking case in the Bible inviting the reader to be aware of how people are bought and sold. The sellers –Jospeh’s brothers and especially Judah – do not want to be known as the culprits. Nobody is willing to admit commiting this crime, instead, one always pretends to be innocent. Meanwhile Joseph’s identity is stripped away as the story continues. Human trafficking, always involves the loss of one’s social networks coupled with elimination of one’s identity. Kata-kata Kunci: Yusuf, Yehuda, hamba, penjualan, identitas, perhambaan, penjual-belian, perdagangan manusia, membunuh, menghilangkan.